Preprečevanje razjed zaradi pritiska - aktivnost zagotavljanja kakovosti na Kliniki za pljučne bolezni in alergijo Golnik - Kadivec, Saša (Obzornik zdravstvene nege, 2000)
The first degree of quality assurance activity is presented, i.e. the selection of adequate processing and the development of standards for sucessful work. The pilot study of the prevention of pressure sores at the University Hospital for Respiratory and Allergic Diseases Golnik is presented.The results were selected according to the method of moment monitoring of all patients due to the criteria selected and with review of nursing documentation. The results obtained are not within the limits of quality, therefore several action steps have been introduced. After a certain time period the measures should be repeated in order to find out the effectiveness of the changes performed.
Keywords: Decubitus ulcer; Hospital departments; koža; Lung diseases; Prevention and control; preventiva; Quality of health care; razjede; zdravstveno varstvo